Penggunaan Kecerdasan Buatan Generatif Bagi Peningkatan Kompetensi Guru IPA Dalam Penyusunan Kerangka LKPD - Surya Gumilar; Irma Fitria Amalia; De Budi Irwan Taofik; Iing Mustain (Jurnal Dharma Bhakti Ekuitas, 2026)
Generative Artificial Intelligence (Gen AI) has experienced rapid development in the field of education and learning. The use of Gen AI by teachers, especially science teachers, can improve Technological Pedagogical Content Knowledge (TPACK) competencies that are currently demanded by teachers. This study aims to develop Student Worksheets (LKPD) based on Gen AI to evaluate the assessment of student abilities by science teachers in the context of science education. A qualitative study design was chosen to explore science teachers' experiences of using Gen AI in preparing LKPD. A total of 30 teachers were given an understanding of the use of the Gen AI application through training activities and coaching visits that were part of the lecturer community service activities. The main objective was to analyze several characteristics of the material and the preparation of LKPD with generative artificial intelligence. The preparation of LKPD GenAI is based on four main activities: (1) hypothesis formation, (2) asking GenAI, (3) discussion, and (4) reflection. All stages are linked to the scientific literacy framework and TPACK aspects. The results of the program showed that respondents agreed with the use of GenAI such as ChatGPT for current learning activities. Science teachers' TPACK competencies can improve during the process of developing student worksheets (LKPD) through group discussions. Teachers are able to select statements from ChatGPT based on concepts they already understand. Teachers also gain new knowledge from ChatGPT statements about the concepts they are asking about. Therefore, Gen AI can be used by teachers to optimize the learning process. Keyword: generative artificial intelligence, GenAI, literacy, science education, TPACK.   Abstrak   Kecerdasan Buatan Generatif (Gen AI) telah mengalami perkembangan pesat pada bidang pendidikan dan pembelajaran. Penggunaan Gen AI oleh guru khususnya guru IPA dapat memberikan peningkatan kompetensi Technological Pedagogical Content Knowledge (TPACK) yang menjadi tuntutan guru saat ini.  Studi ini bertujuan untuk menyusunan Lembar Kerja Peserta Didik (LKPD) berdasarkan Gen AI untuk mengevaluasi penilaian kemampuan siswa oleh guru IPA dalam konteks pendidikan sains. Desain studi kualitatif dipilih untuk mengeksplorasi pengalaman guru IPA tentang penggunaan Gen AI dalam penyusunan LKPD. Sebanyak 30 guru diberikan pemahaman tentang penggunaan aplikasi Gen AI melalui kegiatan diklat dan kunjungan pembinaan yang menjadi bagian dari kegiatan pengabdian dosen. Tujuan utamanya adalah untuk menganalisis beberapa karakteristik materi dan penyusunan LKPD dengan kecerdasan buatan generatif. Penyusunan LKPD GenAI didasarkan pada empat aktivitas utama: (1) pembuatan hipotesis, (2) bertanya kepada GenAI, (3) diskusi, dan (4) refleksi. Seluruh tahapan dikaitkan dengan kerangka literasi sains dan aspek TPACK. Hasil program menunjukkan bahwa responden setuju penggunaan GenAI seperti ChatGPT untuk kegiatan pembelajaran saat ini. Kompetensi TPACK guru IPA dapat mengalami peningkatan selama proses penyusunan LKPD melalui proses diskusi kelompok. Guru mampu menyeleksi pernyataan dari ChatGPT dengan konsep yang telah mereka pahami. Guru juga mendapatkan pengetahuan baru dari pernyataan ChatGPT tentang konsep-konsep yang mereka tanyakan. Sehingga, Gen AI dapat digunakan oleh guru untuk mengoptimalkan proses pembelajaran. Kata kunci: Generatif Kecerdasan Buatan, GenAI, literasi, pendidikan sains, TPACK.